Inhibition of Calpain Prevents Manganese-Induced Cell Injury and Alpha-Synuclein Oligomerization in Organotypic Brain Slice Cultures - Xu, Bin; Liu, Wei; Deng, Yu; Yang, Tian-Yao; Feng, Shu; Xu, Zhao-Fa (PLOS ONE, 2015)
Overexposure to manganese has been known to promote alpha-synuclein oligomerization and enhance cellular toxicity. However, the exact mechanism of Mn-induced alpha-synuclein oligomerization is unclear. To explore whether alpha-synuclein oligomerization was associated with the cleavage of alpha-synuclein by calpain, we made a rat brain slice model of manganism and pretreated slices with calpain inhibitor II, a cell-permeable peptide that restricts the activity of calpain. After slices were treated with 400 μM Mn for 24 h, there were significant increases in the percentage of apoptotic cells, lactate dehydrogenase release, intracellular [Ca2+]i, calpain activity, and the mRNA and protein expression of calpain 1 and alpha-synuclein. Moreover, the number of C- and N-terminal fragments of alpha-synuclein and the amount of alpha-synuclein oligomerization also increased. These results also showed that calpain inhibitor II pretreatment could reduce Mn-induced nerve cell injury and alpha-synuclein oligomerization. Additionally, there was a significant decrease in the number of C- and N-terminal fragments of alpha-synuclein in calpain inhibitor II-pretreated slices. These findings revealed that Mn induced the cleavage of alpha-synuclein protein via overactivation of calpain and subsequent alpha-synuclein oligomerization in cultured slices. Moreover, the cleavage of alpha-synuclein by calpain 1 is an important signaling event in Mn-induced alpha-synuclein oligomerization.